Correlation of Ultrasonically Determined Bladder Wall Thickness and Prostatic Calcification With the Urinary, Psychosocial Dysfunction, Organ Specific, Infection and Neurological/Systemic Symptoms, and Tenderness Scoring System - AKDENİZ, ESRA (ELSEVIER SCIENCE INC, 2019)
OBJECTIVE To evaluate ultrasonically determined bladder wall thickness (BWT) and prostatic calcification presence, in men with chronic prostatitis/chronic pelvic pain syndrome (CP/CPPS), and to correlate the findings with patient characteristics and the urinary, psychosocial dysfunction, organ specific, infection and neurological/systemic symptoms, and tenderness (UPOINT) classification system. MATERIAL AND METHODS Between January 2008 and December 2017, data of 1294 patients diagnosed with chronic prostatitis, in a single urology clinic, meeting a number of selective inclusion/exclusion criteria, were retrospectively analyzed. Patients, compliant to fill out all requested questionnaires, between the ages of 21-65 years were included to the study. Exclusion criteria were noncompliance of filling out required questionnaires, acute and/or chronic bacterial prostatitis, history of genitourinary cancer, history of recent prostate surgery, and diagnosis of neurological diseases affecting the bladder. RESULTS The median patient age and UPOINT subdomain was determined as 37 (IQR = 13, range 21-65) and 2 (IQR = 1, range 0-5), respectively. Median values for BWT, National Institute of Health-Chronic Prostatitis Symptom Index (NIH-CPSI), and International Index of Erectile Function were 3 (IQR = 1, range 2-6, 7), 4 (IQR = 6, range 1-23), and 25 (IQR = 10, range 1-30), respectively. The presence of calcification demonstrated a significant association with total NIH-CPSI score and BWT, whereas its relation with age and total UPOINT score was insignificant. However in contrast to calcification status, BWT >= 3.3 showed a strong and statistically significant relation to all the described measurements. CONCLUSION Measurement of BWT can be used as an accessible and objective method for the diagnose of CP/CPPS according to UPOINT scoring system. (C) 2018 Elsevier Inc.
Keywords: PELVIC PAIN SYNDROME; TRACT SYMPTOMS; RESIDUAL URINE; ALPHA-BLOCKER; UPOINT; MEN; DOMAIN; CLASSIFICATION; PHENOTYPE; THERAPY